Living Faith: Faith of the Burgher Community of Sri Lanka - P. A.Vimukthinie N. Nonis (Publikasi Indonesia, 2024)
Religious education, religion and philosophy, and spirituality in individuals and families are current and pertinent to Sri Lanka today. The topic will discuss the religious faith of the Dutch Burgher community in Sri Lanka. It will investigate whether Dutch Burghers’ have been impacted by Christianity. The objective of the study is to ascertain whether moral, Christian, and social values, crucial for the development of an individual's spiritual life or personality, are derived from religious faith and spirituality, which are associated with personality formation. Carl Muller’s trilogy- The Jam Fruit Tree, Yakada Yaka and Once Upon A Tender Time a rigorous account of the Burgher community, will be used to analyze this in light of Sri Lankan fiction. The trilogy will be textually evaluated as part of the methodology by applying post-colonial and psychoanalytic theories. It will also offer a sociological examination of the Dutch Burgher community in Sri Lanka. The study aims to explore whether religion has influenced the development of the faith of the Dutch Burgher population in Sri Lanka and whether the Catholic environment Dutch families, the Catholic environment, and the clergy have contributed to the creation of responsible, socially acceptable individuals. According to the study, citizens engage in religious activities on various days, months, and seasons as part of their routine. Consequently, religion has devolved into something shallow. It will look into whether Dutch Burghers are spiritually and religiously hybrid, as Bhabha claims, or if they are victims of modernism and are not actual Christians. The study concludes with a specific reference to Carl Muller’s trilogy Christianity had no bearing on the lives of Sri Lanka's Dutch Burgher community or the formation or development of any faith.